Athletes Care Program (SAE) - Puig, F. de (6. Forum on Elite Sport- IAHPSTC, Colorado Springs, USA, 9.-13. September 2009, 2009)
The comprehensive training of athletes is one of the priorities of the CAR of Sant Cugat: The need to help sportspersons achieve a complete preparation in learning habits, for better adaptation to the outside World, were the main reasons why the CAR of Sant Cugat believes that a project like this was necessary. It was important to us that similar programs existed in other countries like Canada, Australia, New Zealand and France. The SAE has shifted in parallel eyes to the business world to go beyond the guidance and backing the sportspersons. Therefore SAE (Athletes Care Program) seeks the involvement of the business world in the overall education of the sportspersons, while providing the company with skilled worker with values, characteristic of high-level sports, which will be beneficial in the business world.